Kebijakan Luar Negeri Amerika Serikat era Donald Trump: Kajian mengenai Faktor Psikologis dalam Free and Open Indo Pacific - Sudirman, Arfin; Dermawan, Windy; Nur Salsabila, Fairuz Nadhira (Universitas 17 Agustus 1945 Jakarta, 2024)
The Indo-Pacific region is an area that connects the Indian and Pacific Oceans so that it has a strategic geopolitical and geo-economics’ position. This region became the center of rapid growth, giving rise to a hierarchy for the United States as a great power country. This is demonstrated by the emergence of the Free and Open Indo-Pacific policy in the era of Donald Trump. This research aims to analyze psychological factors in US foreign policy under Donald Trump through the The Policy of Free and Open Indo-Pacific. This research uses the theory of leaders in foreign policy decision-making. This paper uses qualitative methods by collecting data through interviews with several informants and documentation studies. This research found that the Free and Open Indo-Pacific policy was considered more aggressive due to the influence of psychological factors from Donald Trump, ranging from idiosyncratic factors such as the nature and character of Donald Trump to external factors such as business background and relations between the United States and other countries.